Assessment of Patient Satisfaction and Oral Health-Related Quality of Life Following Full Mouth Rehabilitation with Implant-Supported Prostheses - Ban A. Almudarris; Pooja S. Poonia; Atik H. Mansuri; Sultan A. Almalki; Shekhar Gupta; Rajat Mohanty; Ramanpal S. Makkad (Wolters Kluwer Medknow Publications, 2024)
Background: The concept of success is typically established by the researcher or the practitioner rather than the patient, who has the greatest stake in the outcome of the prosthodontics therapy. Aim: To assess patient satisfaction and oral health-related quality of life (OHRQoL) in following full mouth rehabilitation with implant-supported prostheses (ISP). Methods and Materials: Thirty-two patients who underwent full mouth rehabilitation with ISP were included in this study. The Oral Health Impact Profile-14 (OHIP-14) questionnaire was used for the assessment of patient satisfaction and OHRQoL following full mouth rehabilitation with ISP. Results: The functional limitation among study participants before, 1 month, and 3 months after ISP was 2.1 ± 1.3, 1.5 ± 0.8, and 1.4 ± 0.9, respectively. There was a significant reduction in functional limitation, psychological disability, and social disability before and 3 months after ISP. Conclusion: There is a significant improvement in patient satisfaction and OHRQoL in following full mouth rehabilitation with ISP.